Elevated lncRNA-UCA1 upregulates EZH2 to promote inflammatory response in sepsis-induced pneumonia via inhibiting HOXA1. (8th February 2022) - Zhang, Xiaoqin; Tang, Xuemei; Pan, Lingai; Li, Yongheng; Li, Junlei; Li, Chunling
Abstract: Sepsis is characterized by a dysregulated inflammatory response. We aimed to explore the role of the long noncoding RNA urothelial carcinoma associated 1 (lncRNA UCA1)/enhancer of zeste homolog 2 (EZH2)/homeobox A1 (HOXA1) axis in sepsis-induced pneumonia. The sepsis rat models and RLE-6TN cellular sepsis-induced pneumonia models were established using ligation and puncture (CLP) and lipopolysaccharide (LPS). The expression of UCA1, EZH2, and HOXA1 in rat lung tissues and RLE-6TN cells was detected. Then, the CLP rats were respectively treated with lentivirus to upregulate or downregulate the expression of UCA1 and EZH2 to measure their roles in the pathology, apoptosis, inflammation and phosphorylated NF-κB p65(p-p65) levels in CLP rat lung tissues. UCA1 and EZH2 expression was upregulated or downregulated in LPS-induced RLE-6TN cells to explore their effects on cell viability, apoptosis, inflammation and p-p65 levels. The interactions among UCA1, EZH2, and HOXA1 were identified. UCA1 and EZH2 were upregulated whereas HOXA1 was downregulated in CLP rat lung tissues and LPS-induced RLE-6TN cells. Elevated UCA1 or increased EZH2 aggravated pathology and promoted apoptosis, inflammation and phosphorylated NF-κB p-65 levels in CLP rat lung tissues, and inhibited viability while facilitated apoptosis, inflammation and phosphorylated NF-κB p-65 levels in LPS-induced RLE-6TN cells. Silenced EZH2 reversed the effects of UCA1 elevation on sepsis-induced pneumonia. UCA1 suppressed HOXA1 expression through physically interacting with EZH2. UCA1 overexpression upregulates EZH2 to repress HOXA1 expression, thus aggravating the progression of sepsis-induced pneumonia, which could be alleviated by EZH2 inhibition. Graphical Abstract: